Johnston's organ as a mechanosensory element for spatial orientation in Rhodnius prolixus (2016)
"Our research's aim was to determine if the Johnston's organ (JO) of Rhodnius prolixus, being a complex of mechanosensory neurons, could act as a graviceptor bringing informatlon about the direction of gravity, and thus helping the insect to monitor its spatial orientation. In order to establish if the JO in R. prolixus can perform as a graviceptor, it is necessary to study the process of transduction of the gravity force. Transduction process of any stimulus has three phases as reported by Yack (2004): 1) Coupling, how certain part of the body has a structural configuration allowing it to link the stimulus with the sensory neurons. 2) Transduction, how mechanical displacement of the neuron results in variation of membrane potential. 3) Coding, production of specific patterns of electrical impulses. Our study focusses in the coupling process of sensing gravity force with the antenna. In this phase it ts necessary to know the external structure of the antenna then the way it is affected by the stimulus action and finally the internal structure, meaning the organization and anchoring point of the JO."